Marketing Management as the Realization Process of Research, Production and Sale Activity of the Enterprise - Kireev, Vasiliy S.; Nekrasova, Marina L.; Shevchenko, Ekaterina V.; Alpatskaya, Irina E.; Makushkin, Sergey A.; Povorina, Elena V. (International Review of Management and Marketing, 2016)
Marketing management in the process of implementing is the organization and management system of production and sale's activity of the enterprises, market research for the purpose of formation and satisfaction of demand for production and services and make profit. As a function of management, marketing is no less important than any activity associated with the finance, manufacturing, research, logistics and others. As the management concept (business philosophy) marketing requires the “to vote” for the necessary to them product by the money. This determines the company success and optimally satisfies the customer's needs. Since marketing is the way to convince the masses to purchase, the majority erroneously identified this concept with sales and promotion. The difference lies in the following: sales mainly involves face-to-face contact – the seller has to deal with potential the buyers. Marketing uses the media and other ways to capture the attention and convince many people – people who may not have any direct contact with any of the companies of the marketer by creating demand. One of the leading theorists on management problems, Peter Drucker, says it this way: The marketing purpose is to make efforts on unnecessary sales. Its purpose is so good to know and understand the customer that the product or service will exactly fit the last and sell themselves. Keywords: marketing, management, production, marketing activity JEL Classifications: M31, M37, O30